1998
DOI: 10.3186/jjphytopath.64.160
|View full text |Cite
|
Sign up to set email alerts
|

Release of Cell Wall Degrading Enzymes from Conidia of Blumeria graminis on Artificial Substrata.

Abstract: Cellulase and pectinase activities were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 19 publications
2
15
0
1
Order By: Relevance
“…This may be due to the antigen(s) being too diffuse for visible immunofluorescence prior to induction of germination, or, more likely, the absence of cellulase enzymes at this time. Indeed, this is supported by the recent work of Suzuki et al [22 ] who reported the release of exudates with cellulase activity at 1, 6 and 16 hpi on cellulose membrane but no surface cellulase activity in ungerminated spores. However, Suzuki et al [22 ] found evidence for cellulase activity in homogenized conidia.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This may be due to the antigen(s) being too diffuse for visible immunofluorescence prior to induction of germination, or, more likely, the absence of cellulase enzymes at this time. Indeed, this is supported by the recent work of Suzuki et al [22 ] who reported the release of exudates with cellulase activity at 1, 6 and 16 hpi on cellulose membrane but no surface cellulase activity in ungerminated spores. However, Suzuki et al [22 ] found evidence for cellulase activity in homogenized conidia.…”
Section: Discussionsupporting
confidence: 72%
“…Indeed, this is supported by the recent work of Suzuki et al [22 ] who reported the release of exudates with cellulase activity at 1, 6 and 16 hpi on cellulose membrane but no surface cellulase activity in ungerminated spores. However, Suzuki et al [22 ] found evidence for cellulase activity in homogenized conidia. Taken collectively, these data imply that cellulases are '' released '' from the primary and appressorial germ tubes but not in the liquid exudate released by ungerminated conidia upon initial contact with cellulose membrane [22 ].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Suzuki et al (1998) have shown that B. graminis germlings secrete carboxymethyl cellulases and exo-␤-glucanases during germination. Immunolocalization studies have confirmed the presence of cellobiohydrolase I and II at the tips of primary and appressorial germ tubes (PryceJones et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…tritici 43 , and apple scab fungus Venturia inaequalis 47 , has also been initiated. An exoPG from mycelia of the V. pirina 20 and 3 endoPGs from mycelia of the V. nashicola races 1, 2 and 3 were also previously purified 20 .…”
Section: Introductionmentioning
confidence: 99%